Clinicopathologic Characteristics of Late Acute Antibody-mediated Rejection in Pediatric Liver Transplantation. Issue 9 (September 2021) - Zhou, Shengmei; Mitsinikos, Tania; Emamaullee, Juliet; Weaver, Carly; Wang, Larry; Shillingford, Nick; Warren, Mikako; Bawab, Julie Huss; Tiwari, Nishant; Genyk, Yuri; Thomas, Danny; Parham, David M.
Abstract : Background: An early and accurate diagnosis of liver antibody-mediated rejection (AMR) followed by timely intervention is important for clinical management but remains challenging. The aim of this study was to assess the clinicopathologic characteristics and outcomes of late acute AMR in pediatric liver transplantation recipients. Methods: We performed a retrospective review of 739 ABO-identical/compatible allograft liver biopsies from 199 pediatric transplantation recipients. Results: Based on Banff 2016 AMR criteria, 3 recipients fulfilled the criteria for definite for late acute AMR, 2 met the criteria for suspicious for AMR, and 2 were indeterminate for AMR. We further assessed the clinicopathologic characteristics of these 7 patients. All 7 patients had at least 1 biopsy with a histopathologic pattern compatible with acute AMR. Additionally, we observed accompanied moderately to markedly dilated portal/central veins and endothelialitis disproportionate to the degree of bile duct injury in all 7 patients; periportal/perivenular hepatocyte necrosis was seen in 6 of 7 patients; and arteritis was seen in 3 of 7 patients. In each case, microvascular C4d deposition was present in at least 1 biopsy. Posttransplant donor specific anti-HLA antibodies were detected in 5 patients. Two of 7 patients were retransplanted, and 2 died after developing refractory AMR. The remaining 5 patients were alive with stable graft function at a median follow-up of 4.1 years. Conclusions: Our data suggest that acute AMR in pediatric liver grafts is rare, can develop late, and may be associated with graft loss or patient death. The recurrent histopathologic findings of moderately to markedly dilated portal/central veins and endothelialitis disproportionate to the degree of bile duct injury are features that appear unique to pediatric acute AMR of liver grafts.